Genetic Diversity and Canopy Management in Jack Fruit (Artocarpus heterophyllus Lam.) - Muthulakshmi P (Department of Pomology and Floriculture, College of Horticulture, 2003)
The present investigations on genetic diversity and canopy management in jack fruit (Artocarpus heterophyllus Lam.) was undertaken in the Department of Pomology and Floriculture, College of Horticulture, Vellanikkara, during 1998 to 2002. Major objectives of the study were to explore the variability in vegetative, floral, fruiting and biochemical characters of jackfruit through a comprehensive survey in four different topographical regions of Thrissur district, namely, plains, hills, coastal and riverside areas and to .select quality types, to ascertain the optimum degree and frequency of canopy manipulation and to characterize the firm and soft fleshed types through morphological observations, anatomical and biochemical analysis. Variation was noticed with respect to tree vigour (low, medium and high), canopy shape (pyramidal, broadly pyramidal, obovate, oblong, semi-circular, elliptical and irregular), tree growth habit (erect, horizontal and drooping), branching density (low, intermediate and high) and branching pattern (erect, opposite, verticiliate, horizontal and irregular). A wide variation was noticed in all the four topographical levels with respect to leaf characters like length, width, length / width ratio, shape, apex shape and base shape. Surveyed accessions were grouped into three based on flowering and bearing season, namely, (1) early flowering (September-October) and bearing (December-February), (2) mid-season flowering (November-January) and bearing (March-Mary) and (3) late flowering (February-March) and bearing (June-August), A sporadic flowering and bearing type was also spotted. Variation was noticed with respect to fruit shape (broadly ellipsoid, oblong, high spheroid, spheroid, ellipsoid, obloid, clavate and irregular), junction of stalk attachment (depressed, inflatened and flatened), fruit rind colour (greenish, greenish brown and greenish yellow), shape of spines (sharp pointed, intermediate and flat),